Transformation of Religious Rituals in Religious Tourism: History of Changes in Understanding and Celebration of Spirituality in the Community of Masjid Agung Banten Lama - Mahendra, Yoga; Jundi, Rachmatullah; Wibowo, Zidan; Tristanty, Nova; Putri, Febriani; Sulasti, Lulu Andriani (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
This study delves into how these transformations impact the spiritual understanding and celebration among the local community surrounding the Masjid Agung Banten Lama. Utilizing a qualitative approach involving interviews, field observations, and documentation, the research incorporates 10 informants as primary data sources alongside secondary sources like scholarly articles. Employing purposive sampling, researchers select samples based on specific criteria. Analysis techniques encompass data collection, reduction, presentation, and conclusion drawing. Findings reveal a shift from a spiritual to a recreational focus in mosque activities, with visitors prioritizing social media photography over pilgrimage. The study underscores the necessity for profound spiritual education, particularly among the youth, to safeguard religious values from commercialization and entertainment influences in religious tourism. Thus, preserving and enhancing spiritual comprehension amid Banten's rapid religious tourism growth is vital for upholding the region's religious traditions' authenticity and sanctity.